2016
DOI: 10.1093/gerona/glw004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Shoe Wearing Patterns Over Time in Older Women: Associations With Foot Pain and Hallux Valgus

Abstract: Background:Foot problems are prevalent in older women and are thought to be associated with footwear. This study examined women’s shoe wearing patterns over time and evaluated associations between footwear characteristics and foot pain and hallux valgus.Methods:Women aged 50–89 years (n = 2,627) completed a survey that included drawings of four toe-box shapes and four heel heights. For each life decade, participants indicated which footwear style they wore most of the time. Foot pain in the past 12 months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 32 publications
5
66
2
Order By: Relevance
“…revealed that women's shoe‐wearing patterns over time consisted of wearing shoes with narrow toe boxes between the ages of 20 and 39, which could be critical for developing hallux valgus in later life. Accumulation of chronic mechanical stimulation provokes bone deformity and increases the chances of middle‐aged women rather than men to develop IN . Another possible explanation for this result is that women may tend to visit hospitals more easily than men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…revealed that women's shoe‐wearing patterns over time consisted of wearing shoes with narrow toe boxes between the ages of 20 and 39, which could be critical for developing hallux valgus in later life. Accumulation of chronic mechanical stimulation provokes bone deformity and increases the chances of middle‐aged women rather than men to develop IN . Another possible explanation for this result is that women may tend to visit hospitals more easily than men.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a higher proportion of females in the IN group than in the control group. Menz et al 11 revealed that women's shoe-wearing patterns over time consisted of wearing shoes with narrow toe boxes between the ages of 20 and 39, which could be critical for developing hallux valgus in later life. Accumulation of chronic mechanical stimulation provokes bone deformity and increases the chances of middle-aged women rather than men to develop IN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some evidence that the use of high heels diminishes with age. A survey of 2,627 women aged 50 years and over found that the use of high heels was common between the ages of 20 to 29, but declined to less than 10% by the age of 40 years [73]. This may be indicative of a life-course trajectory in which the influence and perceived importance of fashion diminishes over time and is replaced with a greater emphasis on comfort and practicality.…”
Section: Footwear Considerationsmentioning
confidence: 99%
“…According to another study, the women age between 20 and 29 wear high heel and developed hallux valgus in later age [8]. Mechanism of causing back pain by high heeled shoes was explained by Weitkunat and colleagues in their study in which 23 female participants were included and influence of high heeled shoes were investigated on the sagittal balance of the spine and the whole body [9].…”
Section: What Evidence and Literature Saymentioning
confidence: 99%